Resistance of Mocca Band Against the Indonesian Music Industry (Case Study About Resistance of Mocca Band Dealing with Indonesian Music Industry) - ., Naldo (KnE Social Sciences, 2018)
This study elaborates about the resistance of indie band dealing with the mainstream music industry in Indonesia. The primary subject of this research is Mocca, the indie band from Bandung as the agents of change in the structuration of Indonesian music industry. This study is a qualitative research with case study design. This study discusses about how Mocca could be a fighter with musical colors contrasted with the trend of Indonesian pop music industry which could be accepted by the community as well as providing a new musical color or a new genre which then helped to diversify the Indonesian music industry. Theoretically this study criticized the Indonesian music industry deteriorated in quality. Indie band was born and formed a resistance against the community and the mainstream music tastes of the people that developed due to the influence of music in the media industry. Keywords: resistance, structuration, music industry, independent music